Thermal Energy Storage with Super Insulating Materials: A Parametrical Analysis. (November 2015) - Fantucci, Stefano; Lorenzati, Alice; Kazas, Georgios; Levchenko, Dmytro; Serale, Gianluca
Abstract: The adoption of super-insulating materials could dramatically reduce the energy losses in thermal energy storage (TES). In this paper, these materials were tested and compared with the traditional materials adopted in TES. The reduction of system performance caused by thermal bridging effect was considered using FEM analysis. Afterwards, parametrical analysis of the most influencing variables that affect super insulated TES tanks was carried out, to investigate effective benefits and drawbacks due to the adoption of these materials. Possible future applications and outlooks were discussed.